2021
DOI: 10.1097/nmd.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Pain Intensity, Depression, and Anxiety Levels Among Patients With Chronic Pain During COVID-19 Pandemic

Abstract: Limited data are available for real-world impact of the COVID-19 pandemic on chronic pain patients. This study aimed to evaluate pain intensity, depression, and anxiety status in chronic pain patients during the COVID-19 pandemic. A total of 110 patients with chronic pain participated on a voluntary basis in this questionnaire survey. The questionnaire form elicited information on sociodemographic characteristics and prepandemic and pandemic data on analgesic need, access to medication, visual analog scale (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(75 reference statements)
2
6
0
Order By: Relevance
“…These findings are consistent with studies showing that individuals with chronic pain experience statistically and significantly worse psychological function [ 26 , 27 ]. In fact, similar to previous studies, including those conducted during the first-wave lockdown (e.g., [ 5 , 28 , 29 , 30 ]), the data also showed that chronic pain is a significant predictor of worse psychological function.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with studies showing that individuals with chronic pain experience statistically and significantly worse psychological function [ 26 , 27 ]. In fact, similar to previous studies, including those conducted during the first-wave lockdown (e.g., [ 5 , 28 , 29 , 30 ]), the data also showed that chronic pain is a significant predictor of worse psychological function.…”
Section: Discussionsupporting
confidence: 89%
“…Both increased and decreased pain, anxiety, and depression have been described in chronic pain patients. 40,41 Some patients in the current study reported less pain due to decreased social pressure and an altered perspective on health and wellbeing.…”
Section: Main Findingsmentioning
confidence: 69%
“…Additionally, the majority of patients had their treatments postponed, cancelled, or otherwise made unavailable owing to the pandemic. This serious interruption of treatment may have a negative impact on the health and wellbeing of people suffering from chronic pain [49). Therefore, it should be remembered that, in this study, conducted within the scope of the pandemic, the results may have been influenced by the presence of mental alterations resulting from the conditions of the pandemic [50,51].…”
Section: Discussionmentioning
confidence: 91%